2007
DOI: 10.1086/512854
|View full text |Cite
|
Sign up to set email alerts
|

Coronal "Wave": Magnetic Footprint of a Coronal Mass Ejection?

Abstract: We investigate the properties of two "classical" EUV Imaging Telescope (EIT) coronal waves. The two source regions of the associated coronal mass ejections (CMEs) possess opposite helicities, and the coronal waves display rotations in opposite senses. We observe deep core dimmings near the flare site and also widespread diffuse dimming, accompanying the expansion of the EIT wave. We also report a new property of these EIT waves, namely, that they display dual brightenings: persistent ones at the outermost edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
247
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(272 citation statements)
references
References 37 publications
19
247
2
4
Order By: Relevance
“…In 3D MHD simulations, they found that an electric current shell is formed around an erupting flux rope by return currents (see Figure 44). The shell rotates with the erupting flux rope, which is consistent with the rotation observed in some coronal EUV waves (Podladchikova and Berghmans, 2005;Attrill et al, 2007). A line-of-sight integration of the current shell results in an elliptical pattern that matches observed EUV wavefronts, and both bright and dark patches in two EIT waves could be reproduced quite well.…”
Section: Current Shell Modelsupporting
confidence: 85%
See 1 more Smart Citation
“…In 3D MHD simulations, they found that an electric current shell is formed around an erupting flux rope by return currents (see Figure 44). The shell rotates with the erupting flux rope, which is consistent with the rotation observed in some coronal EUV waves (Podladchikova and Berghmans, 2005;Attrill et al, 2007). A line-of-sight integration of the current shell results in an elliptical pattern that matches observed EUV wavefronts, and both bright and dark patches in two EIT waves could be reproduced quite well.…”
Section: Current Shell Modelsupporting
confidence: 85%
“…This strongly suggests that they correspond to the footpoints of an erupting flux rope that forms the core of a CME (e.g., Sterling and Hudson, 1997;Webb et al, 2000;Mandrini et al, 2005). In addition to these core dimmings, sometimes more widespread and shallow secondary dimmings are observed to trail behind an expanding EUV wavefront (e.g., Delannée and Aulanier, 1999;Wills-Davey and Thompson, 1999;Thompson et al, 2000b;Attrill et al, 2007;Muhr et al, 2011). The interpretation of these features is less clear-cut as in the case of core dimmings.…”
Section: Coronal Dimmingsmentioning
confidence: 99%
“…However, in the common studied case, the 28 October 2003 X17 flare and CME, we have shown that the observed extended dimmings are secondary. The formation of these secondary dimmings can be explained via a stepping reconnection process, similar to the mechanism proposed by Attrill et al (2007) for the bright front and diffuse leading edge of coronal waves. Although magnetic reconnection conserves magnetic flux, one cannot be sure how much of the magnetic flux in the secondary dimmings became part of the CME; therefore, these secondary dimming areas do not provide a proper proxy for magnetic flux measurements to be compared with interplanetary data.…”
Section: Discussionsupporting
confidence: 61%
“…They called such brightenings "stationary brightenings." Later on, such stationary brightenings were confirmed in several observational studies (Delannée 2000;Attrill et al 2007;Delannée et al 2007;Chandra et al 2009). Such a stationary front located at a magnetic separatrix, or a QSL in more general cases, was reproduced in numerical simulations, and can be explained by field-line stretching model (Chen et al 2005(Chen et al , 2006.…”
Section: Discussionmentioning
confidence: 71%